Characterization and Classification of Electrophysiological Signals Represented as Visibility Graphs Using the Maxclique Graph - Rodriguez-Torres, Erika Elizabeth; Paredes-Hernandez, Ulises; Vazquez-Mendoza, Enrique; Tetlalmatzi-Montiel, Margarita; Morgado-Valle, Consuelo; Beltran-Parrazal, Luis; Villarroel-Flores, Rafael (Frontiers in Bioengineering and Biotechnology, 2020)
Detection, characterization and classification of patterns within time series from electrophysiological signals have been a challenge for neuroscientists due to their complexity and variability. Here, we aimed to use graph theory to characterize and classify biological networks using maxcliques as a feature for a deep learning method. We implemented a compact and easy to visualize algorithm and interface in Python. This software uses time series as input that are converted into biological networks. We applied the maxclique graph operator in order to obtain further graph parameters. We extracted features of the time series by processing all graph parameters through K-means, one of the simplest unsupervised machine learning algorithms. As proof of principle, we analyzed integrated electrical activity of XII nerve to identify waveforms. Our results show that the use of maxcliques allows identification of two distinct types of waveforms that match expert classification. We propose that our method can be a useful tool to characterize and classify other electrophysiological signals in a short time and objectively. Reducing the classification time improves efficiency for further analysis in order to compare between treatments or conditions, e.g., pharmacological trials, injuries or neurodegenerative diseases.